(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Summary: Due to the paramount importance of sport and due to the great demand of the world for it, many researchers resorted to developing it in many skills, qualities, players and games until sport became a broad science and was included in university study curricula, and it also has importance on the health of the practicing human. As a result of the importance of these two games (football and volleyball) and the great demand for them, and finding some problems that players face while practicing these two sports, the researcher resorted to finding some problems regarding the (transitional speed) that he got to know through the performance of the players and the team while practicing these two sports and making a comparison between them in regards to (transitional velocity). The researcher investigated and used tests and experiments to reach a comparison between the transitional speed of football players and volleyball players and falling on and strengthening weaknesses and strengths and enhancing them due to the importance of.